2021
DOI: 10.1002/jbt.22778
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 inhibits RANKL‐induced osteoclastogenesis by regulation of mitochondrial apoptosis and oxidative stress in RAW264.7 cells

Abstract: Coenzyme Q10 (CoQ10) has been reported to improve bone density and the number of trabeculae in postmenopausal osteoporosis, but the mechanism remains to be elucidated. We aimed to investigate the effects of CoQ10 on receptor activator of NF-κB ligand (RANKL)-induced osteoclastogenesis and the underlying molecular mechanisms. RAW264.7 cells were treated with different concentrations of RANKL to differentiate into osteoclasts, and then these cells were treated with different concentrations of CoQ10 with or witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Nrf2 downregulates the expression of cytokines involved in osteoclastogenesis and induces the transcriptional activation of antioxidant genes; for this, the reduced expression of Nrf2, present in oxidative stress conditions and detected in osteoporotic rats, causes an increase in osteoclastic formation [ 50 , 51 , 52 , 53 ]. H 2 O 2 stimulates osteoclastogenesis by increasing the expression of osteoclastic differentiation factors by activating the transcriptional factor nuclear factor kappa B (NF-kB) and reducing the expression of Nrf2 in mouse mononuclear macrophage (RAW264.7) cells [ 54 , 55 ]. ROS-activated NF-κB can stimulate the expression of transcriptional factors c-Fos and nuclear factor of activated T-cell cytoplasmic 1 (NFATc1), which regulates the genes involved in osteoclastogenesis and bone resorption, such as tartrate-resistant acid phosphatase and cathepsin K. Moreover, ROS induce the expression of an activator of NF-kB, TNF receptor associated factor 6 (TRAF-6), which RANKL recruits through RANK with a consequent increase in osteoclastic formation [ 55 , 56 ].…”
Section: Oxidative Stress and Osteoporosis: Principal Involved Molecu...mentioning
confidence: 99%
“…Nrf2 downregulates the expression of cytokines involved in osteoclastogenesis and induces the transcriptional activation of antioxidant genes; for this, the reduced expression of Nrf2, present in oxidative stress conditions and detected in osteoporotic rats, causes an increase in osteoclastic formation [ 50 , 51 , 52 , 53 ]. H 2 O 2 stimulates osteoclastogenesis by increasing the expression of osteoclastic differentiation factors by activating the transcriptional factor nuclear factor kappa B (NF-kB) and reducing the expression of Nrf2 in mouse mononuclear macrophage (RAW264.7) cells [ 54 , 55 ]. ROS-activated NF-κB can stimulate the expression of transcriptional factors c-Fos and nuclear factor of activated T-cell cytoplasmic 1 (NFATc1), which regulates the genes involved in osteoclastogenesis and bone resorption, such as tartrate-resistant acid phosphatase and cathepsin K. Moreover, ROS induce the expression of an activator of NF-kB, TNF receptor associated factor 6 (TRAF-6), which RANKL recruits through RANK with a consequent increase in osteoclastic formation [ 55 , 56 ].…”
Section: Oxidative Stress and Osteoporosis: Principal Involved Molecu...mentioning
confidence: 99%
“…RANKL is an important regulator of osteoclastogenesis. On the basis of our previous study, we confirmed that the optimal concentration of RANKL for promoting osteoclastogenesis was 50 ng/mL (11). To further determine the effects of CoQ10 on osteoclastogenesis, 10 -3 M CoQ10 was administered, after which TRAP staining and MTT assays were performed.…”
Section: Coq10 Inhibited Rankl-induced Osteoclastogenesismentioning
confidence: 52%
“…An increasing body of data suggests that CoQ10 contributes to the inhibition of osteoclast differentiation by decreasing the expression of genes encoding osteoclast markers, but the exact mechanism is not known. A number of mechanisms have been reported, including a reduction in bone malondialdehyde levels along with an increase in superoxide dismutase levels, regulation of mitochondrial apoptosis, and suppression of ROS production (11,27,28). On the basis of our previous study, CoQ10 may inhibit RANKL-induced osteoclastogenesis by regulating mitochondrial apoptosis and oxidative stress in RAW264.7 cells (11).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations